Effect of Partial Replacement of Maize with Maize cob - Molasses (Mcmolas) Meal on the Haematology and Biochemistry of Weaner Pigs - Abiloro, O. B.; Akinsola, K. L.; Natheniel, J.; Oyedeji J. O. (Nigerian Journal of Animal Science and Technology (NJAST), 2021)
This experiment was conducted to determine the effect of partial replacement of maze with Maize cob-Molasses (MCMOLAS) meal in the diet of weaner pigs on their haematological and some biochemical indices on sixteen composite breed of pigs with an average weight of 8.12 kg ±0.5, the experiment lasted for a period of 84 days. MCMOLAS meal was prepared by mixing milled maize cobs and molasses in a ratio of 4:1 and pre-digested with an enzyme (cellulase) at 0.5 g/kg and ensiled in air tight container for 7days, sundried and stored for the feeding trial. Proximate composition of the MCMOLAS meal was determined before its inclusion in their diets. Four (4) pigs were allocated to each dietary treatment at 0, 15, 30 and 45% of MCMOLAS meal partially replacing maize in a completely randomized design (CRD). Results showed that the values obtained for haematological indices measured varied significantly (P<0.05) among the dietary treatments except for lymphocyte (LY) and monocyte (MO), RBC, Hb, WBC, GR, MCHC all increased as the level of MCMOLAS meal increased in the diet, whereas, MCH, MCV, MPV, PCT,PLT and PDW decreased, HCT differed across the treatments. Most biochemical indices (TP, ALB, GLO, HDL, LDL and CHOL) were not statistically (P<0.05) influenced by the MCMOLAS meal except glucose which decreased as the level of MCMOLAS meal increased. It was concluded that MCMOLAS meal can be incorporated at 15% into the diet of pigs without adverse effect on their health and well-being.